Based on the marketing of Mochi desserts prepared with salvadoran ingredients. - Iraheta Calderón, Estefany Carolina; Abrego García, Lisbeth Dayana; Erroa Rodas, Emerson Vidal (Universidad de El Salvador. Facultad de Ciencias y Humanidades., 2025)
Disponible en soporte impreso.